Improvement of water quality at drinking water treatment plants intakes on the River Nile - Nourhan Fekry Ali Abdou; Sabry Zaghloul Wahba; Zeinat Kamel Mohamed (Cairo : Nourhan Fekry Ali Abdou, 2021)
Laboratory experiments were performed to study the effects of ultrasonic on the raw water quality by exposure to different time intervals (15,30,45,60 min) at various frequencies (20,40, 60 KHz). The study revealed that there was a positive correlation between ultrasonic intensity, sonication time and bacterial removal. Also, there was clear morphological changes in Nile water algae and blue green algae strains. No change was detected in chlorophyll 2a3 content of Nile water algae, while, remarkable decrease in chlorophyll "a" content of blue green algae strains was detected. There were a reduction in the alum dose and disinfectant byproducts formation. Finally, Ultrasound is an environmentally friendly due to no chemicals were added
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Botany - Microbiology
Issued also as CD
Keywords: Coliform; Fecal Streptococcus; Ultrasonic